Impacts of indoor surface finishes on bacterial viability. (13th May 2019) - Hu, Jinglin; Ben Maamar, Sarah; Glawe, Adam J.; Gottel, Neil; Gilbert, Jack A.; Hartmann, Erica M.
Abstract: Microbes in indoor environments are constantly being exposed to antimicrobial surface finishes. Many are rendered non‐viable after spending extended periods of time under low‐moisture, low‐nutrient surface conditions, regardless of whether those surfaces have been amended with antimicrobial chemicals. However, some microorganisms remain viable even after prolonged exposure to these hostile conditions. Work with specific model pathogens makes it difficult to draw general conclusions about how chemical and physical properties of surfaces affect microbes. Here, we explore the survival of a synthetic community of non‐model microorganisms isolated from built environments following exposure to three chemically and physically distinct surface finishes. Our findings demonstrated the differences in bacterial survival associated with three chemically and physically distinct materials. Alkaline clay surfaces select for an alkaliphilic bacterium, Kocuria rosea, whereas acidic mold‐resistant paint favors Bacillus timonensis, a Gram‐negative spore‐forming bacterium that also survives on antimicrobial surfaces after 24 hours of exposure. Additionally, antibiotic‐resistant Pantoea allii did not exhibit prolonged retention on antimicrobial surfaces. Our controlled microcosm experiment integrates measurement of indoor chemistry and microbiology to elucidate the complex biochemical interactions that influence the indoor microbiome.